47. EVALUATION OF THE RESULTS OF SURGERY OF POSTERIOR VOCAL CORD REMOVAL USING SUCTION CUTTING INSTRUMENTS IN THE TREATMENT OF BILATERAL VOCAL CORD PARALYSIS IN CLOSED POSITION (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the results of posterior vocal cord resection surgery using a suction cutter in the treatment of bilateral vocal cord paralysis in the closed position.Subjects: 21 patients diagnosed with bilateral vocal cord paralysis in the closed position were treated with posterior vocal cord resection using a suction cutter at the Emergency Department, National Otorhinorarynology Hospital of Vietnam from September 2023 to August 2024.Research method: Prospective.Results: Patients with previous tracheostomy were able to remove the cannula a few days after surgery. After surgery, 85.72% of patients, 90.48% of patients no longer had difficulty breathing and had a glottis width > 5 mm; 66.67% of patients had mild or moderate voice disorders.Conclusions: Surgery to resect the posterior part of the vocal cords with a suction cutter gives good results, both resolving dyspnea and preserving speech function, improving the patient's quality of life, short surgery time, and causing few complications.
Keywords: Bilateral vocal cord paralysis; vocal cord resection